2012
DOI: 10.1039/c2cs35043b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and its derivatives: switching ON and OFF

Abstract: As the thinnest material ever known in the universe, graphene has been attracting tremendous amount of attention in both materials science and condensed-matter physics since its successful isolation a few years ago. This one-atom-thick two-dimensional pseudo-infinite nano-crystal consists of sp(2)-hybridized aromatic carbon atoms covalently packed into a continuous hexagonal lattice. Graphene exhibits a range of unique properties, viz., high three-dimensional aspect ratio and large specific surface area, super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
154
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(157 citation statements)
references
References 206 publications
2
154
0
1
Order By: Relevance
“…Among them, the graphene/graphene−based nanosheets have attracted much attention because of their unique structural features and exceptional chemical, electrical and mechanical properties [11][12][13]. Several kinds of enzymes including horseradish peroxidase (HRP) and lipase have been tentatively immobilized on the graphene/graphene−based nanosheets [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the graphene/graphene−based nanosheets have attracted much attention because of their unique structural features and exceptional chemical, electrical and mechanical properties [11][12][13]. Several kinds of enzymes including horseradish peroxidase (HRP) and lipase have been tentatively immobilized on the graphene/graphene−based nanosheets [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,15 ] Furthermore, graphene can be readily functionalized or modifi ed to exhibit a number of interesting electrical characteristics, [16][17][18] and resistive switching effects in some graphene based materials, for example graphene oxide, have also been reported. [19][20][21] In this study, we show that RRAM devices can be successfully integrated with graphene electrodes in a compact device structure. More importantly, functionalized graphene electrodes exhibit an intrinsic threshold switching behavior analogous to insulator-metal transition (IMT), and provide a built-in selector element for the RRAM devices that is very desirable for mitigating the sneak path problem in crossbar memory arrays.…”
mentioning
confidence: 99%
“…This is due to its unique electrical, mechanical, and thermal properties. [30][31][32] It is reported that the theoretical specic surface area of graphene can reach 2630 m 2 g À1 , even larger than that of a single-walled carbon nanotube (1300 m 2 g À1 ). 33 Those special properties imply that GR has giant potential in the eld of biosensors.…”
Section: -24mentioning
confidence: 99%